Viability of Equine Semen Stored in a Polyethylene System for Transport for Eight Hours - Maciel, Alisson Ceccato; Camargo, Vinicius; Mattos, Rodrigo Costa; Rechsteiner, Sandra Fiala (Acta Scientiae Veterinariae, 2017)
Background: Equine semen storage and shipment, being it colled or frozen, allows the veterinarian to direct matings, providing the use of genetically superior stallions, which are mostly located in breeding stations or training centers. Achieving good pregnancy rates depends, beyond the moment of artificial insemination (AI), on factors related to the semen cooling, such as: system used for transport, cooling rate, final storage temperature, storage time and individual variation among stallions, such as age and resistance to cooling. Based on these aspects, this experiment was conducted in order to test a polyethylene system to ship equine semen. Materials, Methods & Results: A total of 87 ejaculates from five stallions with known fertility were used. The stallions aged between 6 to 14 years old, being three Thoroughbred and two Miniature Pony horse. The ejaculates were collected twice a week using a Hannover artificial vagina. After each collection, the semen sample was macroscopically evaluated for appearance, color and smell. A semen sample was used to evaluate the parameters of total motility, vigor and concentration, being these last three parameters assessed by counting 100 sperm cells for analysis. These analysis were performed using an optical microscope, being the concentration taken with a Neubauer chamber after dilution of 1:20 (semen: citrate formol). Subsequently to this, the semen was diluted 1+1 (diluent+semen) with skim UHT milk, and divided into four aliquots of equal volume, yielding a total of four groups. In the control group (GC) the semen was analyzed immediately after dilution (zero h - 0-h). Samples from other groups were stored for eight h (8-h) in three different devices: Equitainer® (GE), BotuFLEX® (GB) or Polyethylene System - Cooled (SP) and non-Cooled (SPN). During storage of the samples the cooling curve of the system under study was evaluated, using a digital thermometer. To estimate the sperm viability, the parameters of total sperm motility and vigor were evaluated, the integrity of plasma membrane were evaluated using CFDA / PI, and the plasma membrane functionality using the hiposmotic test (HOST), being also examined the percentage of spermatozoa considered morphologically normal (sperm morphology). The SP showed a PM integrity and sperm morphology as the only parameters that did not occur a statistical difference when compared to Equitainer® and the BotuFLEX® (averages of the CFDA/PI = 71.12%, 73.29%, 71.32 and averages of morphology = 80.50%, 82.29% and 81.28%, respective values of each parameter to SP, GE and GB, while SPN showed mean values lower than the GC and GE for all parameters (averages of total motility = 50.65% and 62, 60%; averages of vigor = 1.78 and 2.43; averages of CFDA/PI = 72.56% and 78.30%; averages of HOST = 43.56% and 48.87%; averages of morphology = 77.17% and 84.82%, respectively for SPN and GE). Compared to BotuFLEX®, the SPN had no significant difference only for the parameter of PM functionality (HOST). Discussion: The average temperature of SP was 18.0°C, and the SPN was 18.2°C. The SP was equal or similar to the other used systems, but the SPN showed no difference when compared to PS. However NPS was worse than the other systems from this experiment. These results show that the PS might be an alternative to ship equine semen for eight h, compared to the other cooled systems studied in this work.